SwimTrain: Exploring Exergame Design for Group Fitness Swimming - Choi, Woohyeok; Oh, Jeungmin; Edge, Darren; Kim, Joohyun; Lee, Uichin (2016 CHI Conference on Human Factors in Computing Systems (CHI '16), 2016)
We explore design opportunities for using interactive technologies to enrich group fitness exercises, such as group spinning and swimming, in which an instructor guides a workout program and members synchronously perform a shared physical activity. As a case study, we investigate group fitness swimming. The design challenge is to coordinate a large group of people by considering trade-offs between social awareness and information overload. Our resulting group fitness swimming game, SwimTrain, allows a group of people to have localized synchronous interactions over a virtual space. The game uses competitive and cooperative phases to help group members acquire group-wide awareness. The results of our user study showed that SwimTrain provides socially-enriched swimming experiences, motivates swimmers to follow a training regimen and exert more intensely, and allows strategic game play dealing with skill differences among swimmers. Consequently, we propose several practical considerations for designing group fitness exergames.